Parametric Design of Internal Gears Based on Accurate Tooth Profile Modeling - Cao Dongjiang; Shang Peng; Cui Hongtao; Xi Wenyu (Jixie chuandong)
Aiming at the problems of insufficient modeling accuracy and low efficiency of design verification and calculation in the current parametric design and development of internal gears, a parametric design system of internal gears based on accurate tooth profile modeling is developed by using Matlab GUI. According to the principle of gear generating machining theory, the involute tooth profile of internal gears is generated. The tooth profile-normal method is used to establish the tooth root transition curve equation of internal gears, realizing the accurate modeling of the whole tooth of internal gears, and the pressure angles αM and αN at the transition point of the internal gear profile are calculated. The geometric calculation and interference verification of the design parameters of internal gear pairs are completed through the parametric design program. In the transition curve interference verification part, using the pressure angles αM and αN of the tooth profile transition point, the verification formula of the transition curve interference of the internal gear pair is calculated under the condition of any size tooth top fillet (or unspecified fillet) of the cutter. Finally, the whole tooth profile data of the designed target gear pairs is imported into the Catia interface, and the three-dimensional solid model of the gear pairs is established, which lays a foundation for the subsequent research on the stress analysis and dynamic performance detection of the gear system.